Analisis Penggunaan Gaya Bahasa Sarkasme pada Lirik Lagu Peradaban Karya Feast - M. Nur Kholis; Wawan Hermawan; Seftia Wulan Ayu Ningrum; Mukhammad Aqmal Azis (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Song lyrics are often a vehicle for creatively conveying messages and social criticism. The song Peradaban by Feast is one example, where various forms of satire are delivered in a sharp and meaningful style. This study aims to identify and analyze the use of sarcasm in the song. Using qualitative descriptive methods and semantic approaches, the researcher examines the forms of sarcasm and the meaning behind the lyrics used. The results show that the song contains various types of language styles such as sarcasm, hyperbole, irony, and metaphors that convey concerns about injustice, colonialism, and social identity crises. This study shows that song lyrics can be a powerful medium for voicing social criticism in a subtle but still effective manner.